2009
DOI: 10.1183/09031936.00050009
|View full text |Cite
|
Sign up to set email alerts
|

Parental occupation is a risk factor for childhood wheeze and asthma

Abstract: The present birth cohort study investigated whether or not childhood wheeze and asthma are associated with parental exposure to occupational sensitisers that cause asthma.Parental occupation, from the Avon Longitudinal Study of Parents and Children (ALSPAC), was related to wheeze, asthma, ventilatory function, airway responsiveness and atopic sensitisation in children aged 0-102 months.Occupation was recorded for 11,193 mothers and 9,473 fathers antenatally, and for 4,631 mothers and 5,315 fathers post-natally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 22 publications
2
59
0
Order By: Relevance
“…Moreover, the results of some studies have indicated that early exposure to pesticides up to the age of 4 years is the most relevant time window of exposure [30,31]. It was also shown that contact of the children in the first year of life with a mother who was herself in contact with pesticides in the case of occupational and/or residential exposure was likely to increase the likelihood of wheezing and childhood asthma [39,42], non-infectious cough in children aged 5-6 years [36], and wheezing in children under 18 years of age [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the results of some studies have indicated that early exposure to pesticides up to the age of 4 years is the most relevant time window of exposure [30,31]. It was also shown that contact of the children in the first year of life with a mother who was herself in contact with pesticides in the case of occupational and/or residential exposure was likely to increase the likelihood of wheezing and childhood asthma [39,42], non-infectious cough in children aged 5-6 years [36], and wheezing in children under 18 years of age [43].…”
Section: Discussionmentioning
confidence: 99%
“…High levels of maternal occupational exposure to biocides and fungicides after birth increased the likelihood of wheezing (OR 1.22, 95% CI 1.02-2.05) and childhood asthma at 7.5 years (OR 1.47, 95% CI 1.14-1.88). This exposure, combined with an exposure to latex, increased the likelihood of wheezing during childhood (OR 1.22, 95% CI 1.03-1.43) and asthma at 7.5 years (OR 1 47, 95% CI 1.14-1.47) [42].…”
Section: Studies In Childrenmentioning
confidence: 99%
“…Several factors have been proposed to contribute to the increasing incidence of asthma and AD [eg, maternal smoking (9), alcohol consumption (10), eating habits (11,12), obesity (13), and work environment (14,15)]. Also maternal stress has been suggested to interfere with fetal immune development (16,17).…”
mentioning
confidence: 99%
“…In the automatic mode, the code with the highest score was automatically accepted. This coding strategy has been shown to have 91% agreement with manually coded occupations [20].…”
Section: Occupational Exposurementioning
confidence: 87%